Short communication. Effects of adding different protein and carbohydrates sources on chemical composition and in vitro gas production of corn stover silage - Mejía-Uribe, L. A.; Borquez, J. L.; Salem, A. Z. M.; Dominguez Vara, I. A.; Gonzalez-Ronquillo, M. (Spanish Journal of Agricultural Research, 2013)
The use of protein-rich by-products based in swine manure (SM), poultry waste (PW) or chemicals compounds as urea (U), as well as energy products like molasses (M) and bakery by-product (BB), is a viable method to produce good quality silage. In addition, the use of a bacterial additive can improve the fermentation characteristics of silage. The objective of this study was to determine chemical composition, in vitro gas production (GP) and dry matter disappearance (DMd), using different sources of protein and energy in silage. The silages were made using SM, PW or U as protein sources and M or BB as energy source, with corn stover and with or without a bacterial additive. The organic matter (OM) content was higher (p < 0.001) in silages with UBB, UM and SMBB compared with the rest of the treatments; meanwhile crude protein content was higher (p < 0.001) in silages with U. The addition of a bacterial additive increased (p < 0.05) OM content and decreased (p < 0.05) fiber content. Total GP was higher (p < 0.05) in silages containing BB, but DMd was higher (p < 0.05) in silages with U and SMBB. The inclusion of a bacterial additive decreased (p < 0.05) GP and DMd. The use of alternative sources of protein such as poultry and swine manure or urea, and of by-products of sugar industry and bakery is an alternative for silages based on corn stover. The results show that when properly formulated, the silages can provide more than 16% of crude protein and have DMd values above 60%.